Carrier-Envelope-Phase Controlled Attosecond Pulse Generation by Undulator Radiation - Tibai, Zoltán; Tóth, György; Nagyváradi, Anett; Gyöngy, András; Fülöp, József András; Hebling, János; Almási, Gábor (Frontiers in Physics, 2018)
Practical aspects of the robust method we proposed for producing few-cycle attosecond pulses with arbitrary waveform in the extreme ultraviolet spectral range are studied numerically. It is based on the undulator radiation of relativistic ultrathin electron layers produced by laser-driven energy modulation. By using realistic specifications, we show that isolated waveform-controlled extreme ultraviolet attosecond pulses at 5 nm with 10 nJ energy and 20 as pulse duration, at 20 nm with 90 nJ energy and 80 as pulse duration, and at 60 nm with 200 nJ energy and 240 as duration can be generated, respectively. PACS numbers: 41.60.Cr, 41.50.+h, 41.75.Ht